Durability of Silica Sand-Based Self-Compacting Mortar: A Study on Sorptivity and Chemical Attack - Toluwalope Dominion Zubair; Mutiu Kareem; Abibat Usman; Divine Adejumo; Glory Ponnle; David Adeyeye; Adeleye Akinbade-Ojo (Faculty of Science and Technology, Universitas Sanata Dharma, 2026)
Cement is an essential construction material which serves as the binder in the production of concrete, mortar and bricks production. The production of cement poses a serious issue as it results in the emission of greenhouse gases directly responsible for climate change. In this study, Self-Compacting Mortar (SCM) mixes were developed by incorporating Ground Silica Sand (GSS) of 0 - 10% at a step of 2.5% and Raw Ground Silica Sand (RSS) of 0 - 100% at a step of 25% as replacement for cement and fine aggregate, respectively. The sorptivity and chemical attack via the use of Sodium Chloride (NaCl) on SCM specimens produced from different mixes were determined after 28 and 56 days of curing. The sorptivity of SCM specimens increased at all levels compared to the control when RSS is used as replacement for fine aggregate while the same was experienced when GSS was used as replacement for cement except at the 5% replacement level. All specimens fell under the ASTM standard for sorptivity states that all construction materials must have a water absorption value within 20%. When exposed to chemical attacks, there was an increase in weight loss and compressive strength loss with every increase in percentage replacement while the SCM does not deteriorate rapidly after exposure to NaCl. It can be concluded that GSS and RSS exhibited the potential for application as binder and sand contents in SCM production.